Growing During a Global Crisis - Shahin, Ahmad E (AUC Knowledge Fountain, 2021)
Employing the data from the World Bank Enterprise surveys, we examine how the first shock of the COVID-19 pandemic has affected firm dynamics across the world. Our first group of robust models have tested the effect of internal firms’ managerial decisions and other external factors on the sales’ growth, where we found that the most important decisions are related to preserving and increasing liquidity levels, in addition to utilizing the workforce in giving more input to maintain and grow the firms’ sales. Our second group of robust models have tested the firms’ financial decisions and other external factors on the change of the firms’ liquidity levels, where we found that the firms’ liquidity levels are better protected by maintaining the relationships with financial institutions and government authorities, in addition to international firms through exporting. This paper adds to the literature through its focused examination of the immediate effect of the pandemic on firms during the months May to November 2020, while keeping a broad scope by covering 14,751 firms from 25 economies around the world.